2018
DOI: 10.11648/j.ijae.20180302.11
|View full text |Cite
|
Sign up to set email alerts
|

Rural Financial Inclusion: Prospects and Challenges of Collective Action in Extending Financial Services among Rural Smallholders Farmers in Tanzania

Abstract: The paper presents prospects and challenges of the collective action in facilitating access to financial services among smallholder farmers in rural areas. It is based on data collected through Focus Group Discussions (FDGs) from 11 cases of Savings and Credit cooperatives (SACCOs), Primary Agricultural Marketing Cooperatives (AMCOS) and Farmers Associations (FA) in Dodoma and Morogoro regions in Tanzania. By using the content analysis, the paper presents three major findings. First, the groups are much releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Local unions disseminate information to farmers and help them form interest groups to share and support each other in economic development activities. This result is consistent with the finding by Uronu and Ndiege (2018), which indicated that members of unions help households to strengthen social relations and motivate households to apply agricultural technologies and access markets.…”
Section: Determinants Of Access To Subsidized Creditsupporting
confidence: 92%
“…Local unions disseminate information to farmers and help them form interest groups to share and support each other in economic development activities. This result is consistent with the finding by Uronu and Ndiege (2018), which indicated that members of unions help households to strengthen social relations and motivate households to apply agricultural technologies and access markets.…”
Section: Determinants Of Access To Subsidized Creditsupporting
confidence: 92%
“…iv. Access to and use of credit is reported by Achandi et al (2019), Uronu and Ndiege (2018), Madafu (2015), and Thabiti (2014).…”
Section: Social Differences In Access To and Use Of Improved Agricultural Technologies And Servicesmentioning
confidence: 99%
“…From their 180 randomly selected sample of adult households (male and female), findings shows that poverty rate was higher among women population. Studies like Andrew, et al, [15], [19], [20] [21], [12]; [11], [1] are among similar authors with positive and significant relationship between financial inclusion and economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In order words, the more access to financial related products and services in a country, the likelihood of a country's potentials in achieving growth per capital. While the term (financial inclusion (FI)) has constituted heated debate in development finance lately, [1], [2], [3], Babajide, et al, [4], [5], [6], are considered as some of the discussants. Mainly, summation of these authors is that access to formal bank account opening, usage of banks products and services, quality of products offering, increase number of banks branches, increase in number of payment devices, public awareness to banks products and services and so on, constitute financial inclusion.…”
Section: Introductionmentioning
confidence: 99%